Kuurojen yläasteen oppilaiden kirjoitetun kielen hallinta - Hakkarainen, Liisa (opettaja) (1988)
The purpose of the study was to develop a method for the assessment of deaf pupils' mastery of written language. The principles of the cloze method were adopted in the assessment. The aim was to characterize the features of the Finnish language, and the sentence-processing skills typically commanded by deaf upper-level pupils by using cloze items developed for them. The cloze procedure is by nature a method of assessing integrative reading skills by means of which it is possible to obtain information on pupils' reading processes. The empirical presentation of the study was divided into a comparative and a descriptive part. In the comparative part the level of reading skill among the deaf and aurally non-handicapped pupils (ANH) was studied using the standardized Lukila II-III-test, and comparisons in linguistic abilities were made between similar deaf (N=61) and ANH (N=61) groups having the same reading level. The tests were five cloze tests of a standard format which increased in difficulty. The descriptive part analyzed the mastery of written language by deaf upper level pupils (N=61) and their mastery of certain special features of written language in three cloze tests of increasing difficulty. Linguistic anticipation skill was studied by each sentence constituent and difficult items (percentage of correct answers below 20) in them were scrutinized more closely. Errors in inflection were separately analyzed into nouns and verbs. Furthermore, morphological, semantic and syntactic errors were studied by ability group. According to the results of the comparative part the reading skills, measured by a standardized reading test, of 15-year-old deaf pupils corresponded to that of 8-year-old ANH-pupils (2nd graders). The level of semantic and syntactic-morphological mastery was, however, highly significantly lower in the deaf than the ANH pupils when measured by the cloze procedure, which is far more precise than the standardized reading test. The results of the descriptive part indicated that 35% of the deaf pupils' answers in the cloze test conformed to Finnish. In addition there were less morphological (10%) and semantic (6%) errors. The majority of the answers (48%) were arbitrary completions, not at all applicable in Finnish. Cloze scores varied by parts of speech; so that pronouns were best mastered and adverbs the least. There were no great differences in the mastery of sentence constituents, with the exception of subjects. The level of the simple sentence was mastered best, whereas the level of complex sentences had not been attained during the pupils' period in comprehensive school. Pupils were better able to produce coordinate clauses than subordinate ones. Some consistent completion strategies could be found in the pupils, e.g. they attempted to use the word order SVO (subject - verb - object). Congruence and reaction rules were not sufficiently mastered in inflection. Interference caused by sign language was not significant in the answers.